Human PARP1 substrates and regulators of its catalytic activity: An updated overview - Tao Zhu; Ju-Yan Zheng; Ling-Ling Huang; Yan-Hong Wang; Di-Fei Yao; Hai-Bin Dai (Frontiers in Pharmacology, 2023)
Poly (ADP-ribose) polymerase 1 (PARP1) is a key DNA damage sensor that is recruited to damaged sites after DNA strand breaks to initiate DNA repair. This is achieved by catalyzing attachment of ADP-ribose moieties, which are donated from NAD+, on the amino acid residues of itself or other acceptor proteins. PARP inhibitors (PARPi) that inhibit PARP catalytic activity and induce PARP trapping are commonly used for treating BRCA1/2-deficient breast and ovarian cancers through synergistic lethality. Unfortunately, resistance to PARPi frequently occurs. In this review, we present the novel substrates and regulators of the PARP1-catalyzed poly (ADP-ribosyl)ation (PARylatison) that have been identified in the last 3 years. The overall aim is the presentation of protein interactions of potential therapeutic intervention for overcoming the resistance to PARPi.